The changing monetary environment - D'Souza, Errol (2001)
In the recent past the RBI has been using open market operations to sterilize the inflows of foreign capital so as to contain domestic monetary expansion. Due to a rise in the income velocity of base money this has created an incentive for the government to resort more to market borrowings from banks which has raised real interest rates and which exerts a depressing impact on the growth of economic activity along with creating pressures for the inflation rate to increase. The changed environment calls for a reduction in government expenditures which, whilst reducing interest rates and enhancing the level of economic activity, will also help nudge the economy to a lower inflation level. - Reproduced
Keywords: Monetary policy